2010
DOI: 10.1021/jp101661t
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Phase Separation in Poly(acrylonitrile-butadiene-styrene)-Modified Epoxy/DDS System: Kinetics and Viscoelastic Effects

Abstract: The dynamics of phase separation and final morphologies of poly(acrylonitrile-butadiene-styrene) (ABS)-modified epoxy system based on diglycidyl ether of bisphenol A (DGEBA) cured with 4,4'-diaminodiphenylsulfone (DDS) have been monitored in situ throughout the entire curing process by using optical microscopy (OM), differential scanning calorimetry (DSC), rheometry, and small-angle laser light scattering (SALLS). The evolution of phase separation and final morphologies with substructures were explored by OM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 37 publications
4
46
0
Order By: Relevance
“…This is followed by a crossover point (gelation point) where equals that means the system acts as both elastic and viscous, storing and dissipating an identical amount of energy at this point [14,42]. Epoxy composites with, 0.7, 3.6, and 6.9 wt% TiO 2 follow a similar trend.…”
Section: Nonisothermal Cure Behaviormentioning
confidence: 84%
See 1 more Smart Citation
“…This is followed by a crossover point (gelation point) where equals that means the system acts as both elastic and viscous, storing and dissipating an identical amount of energy at this point [14,42]. Epoxy composites with, 0.7, 3.6, and 6.9 wt% TiO 2 follow a similar trend.…”
Section: Nonisothermal Cure Behaviormentioning
confidence: 84%
“…In this processes, polymer synthesis and shaping take place in a single operation; this involves the conversion of liquid monomers or polymers into solid crosslinked polymers [14,15]. In addition, tendency of polymers to expand or contract during processing is a problem that has been widely recognized, especially for epoxy systems [16,17].…”
Section: Journal Of Polymersmentioning
confidence: 99%
“…The microstructural evolution of the PIPS process can be successfully monitored and has been studied extensively by scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), optical microscopy (OM), rheological dynamic analysis, small-angle laser light scattering, and the combination of the aforementioned analyses. [23][24][25][26][27][28][29] In addition to these methods, cloud-point, dielectric relaxation spectroscopy, and temperature-jump light-scattering and rheometry measurements have also been widely used to investigate PIPS in thermosets. [30][31][32][33][34] Jyotishkumar et al 24 traced the dynamics of phase separation and the final morphologies of a poly(acrylonitrile-butadiene-styrene) (ABS) modified diglycidyl ether of bisphenol A (DGEBA) epoxy system in situ with OM, DSC, rheometry, and small-angle laser light scattering.…”
Section: Overview Of Methods Used To Study the Pips Of Thermosetsmentioning
confidence: 99%
“…The addition of fillers to the epoxy resin systems will alter their morphology and curing kinetics [23][24][25][26][27]. Vijayan et al [26] have investigated the effects of nanoclay and carboxyl-terminated (butadiene-co-acrylonitrile) (CTBN) rubber on the reaction induced phase separation and curing kinetics of an epoxy/cyclic anhydride system using dynamic and isothermal differential scanning calorimetry (DSC), and found that nanoclay surfactant accelerated the cure reaction, whereas the phase-separated CTBN hindered the cure reaction.…”
Section: Introductionmentioning
confidence: 99%